ANALISIS PENENTUAN SEKTOR-SEKTOR UNGGULAN PRIORITAS KABUPATEN KOTAWARINGIN TIMUR - Dwi Ardi Wicaksana Putra; Wehdawati; Sigit Mulyanto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2018)
The determination of priority sectors is very important for accelerating the economic growth in East Kotawaringin Regency. This research is an initial step in providing information on priority sectors which have the potential to be developed through identification and analysis of the development of the base sector; the sectors that have relatively good economic structure and competitiveness as well as the sectors which are classified as the main economic sector groups in each analysis year. The method used is in this research was Loqation Quotient (LQ) analysis, Shift Share analysis and Klassen Typology analysis using data from the East Kotawaringin Regency GRDP and Central Kalimantan Province GRDP at Constant Price (2010) according to the 2011-2016 period. By using these three analyzes, priority sectors are determined by looking at the development experiences or trends that have occurred in 17 economic sectors over the past 5 years. The results of this study indicated that the priority superior sector of East Kotawaringin Regency relies on the sector of Wholesale and Retail Trade; Repair of Motor Vehicles and Motorcycles; Manufacturing; Transportation and Storage; Agriculture, Forestry, and Fishing; as well as Construction